Double disadvantage: the unique challenges Hispanics with disabilities face in the workplace - Lovato, Christopher L., author; James, Keith, advisor (Colorado State University. Libraries, 2004)
This dissertation examines an expected interaction between ethnicity and disability status when predicting organizational decisions. Specifically, two studies investigated whether "double disadvantage" effects occur among Hispanics with disabilities. In Study 1, data from 27 million individuals in the 2000 U.S. Census revealed a lower rate of employment and a higher rate of poverty for Hispanics with disabilities as compared to reference groups (i.e., Hispanics without disabilities. Whites with disabilities, and Whites without disabilities). Further, Hispanics with a disability had an employment rate that was 26% lower and a poverty rate that was 126% higher than expected based on their proportion in the total population. As hypothesized, a significant interaction between ethnicity and disability status was found. In addition, exploratory analyses found a significant 3-way interaction between ethnicity, disability status, and sex. In Study 2, a within subjects design was used with a paper-people methodology. Specifically, 157 managers with experience in selection made employment decisions based on fictitious resumes reflecting Hispanics with disabilities and the reference groups (i.e., Hispanics without disabilities, non-Hispanics with disabilities, and non-Hispanics without disabilities). Each manager reviewed four fictitious resumes (one from each group) and recommended whom to interview, whom to select into two job levels, starting salary, number of stock options granted, and placement into a development program. Hispanics with disabilities were hypothesized to experience more negative outcomes than the reference groups. The hypotheses were not supported and double disadvantage effects were not found in Study 2. In fact, Hispanics were recommended more often than non-Hispanics for interviews granted, higher level job placements, and inclusion in development programs. Discrepancies in the results of the two studies may be attributed to the organizational access outcomes used, social desirability effects, or methodological limitations. Implications of the research as well as future research suggestions are discussed.
Keywords: social psychology; studies; African Americans; racism; minority and ethnic groups; multiculturalism and pluralism; disabled people; bias; white people; Hispanic people